Intercomparison of radon and radon progeny concentration measurements performed in the Historic Silver Mine in Tarnowskie Góry, Poland - Navratilova Rovenska, Katerina; Slezakova, Miriam; Vignaud, Caroline; Blanchart, Pascale; Wołoszczuk, Katarzyna; Hoftuft, Jostein; Grygier, Agata; Skubacz, Krystian; Vargas, Arturo; Maiorana, Andrea; Gruber, Valeria; Gräser, Joachim; et al. (Frontiers in Public Health, 2025)
IntroductionIn the frame of the RadoNorm project, within work package 5.4, an intercomparison of radon and radon progeny measurements was organized in the Historic Silver Mine in Tarnowskie Gory (Poland). The aim of this intercomparison campaign was to compare the results of different electronic monitors for measurement of radon and radon progeny concentration under field conditions of an underground workplace over 3 days of measurements.MethodsIn total, nine laboratories from seven European countries participated in the intercomparison study contributing with sixteen continuous radon monitors, ten radon progeny continuous monitors, and one TLD-based integrating system for PAEC measurements.ResultsDespite the short duration of the field campaign, the comparison of radon activity concentration measurements showed strong consistency across most instruments, although notable deviations were observed with three instruments. Radon equivalent equilibrium concentration measurements also demonstrated good agreement, with only one outlier among ten instruments. Comparison of short term averages of EEC (PAEC) obtained from continuous monitors and integral TLD based Alpha probes showed good agreement. Greater variability was observed in the results for unattached radon progeny.DiscussionThis intercomparison also allowed of testing instrument's responses in extreme ambient conditions with high humidity and relatively low temperature that are at the edge of the instrument's operating conditions.